EDUKASI BERBASIS VIDEO DALAM MENINGKATKAN KEPATUHAN MINUM OBAT PADA PENDERITA DIABETES MELLITUS - Heltty, Heltty; Rohaendi, Hendi; Madame, Yayan Herdianto; Mirad, Mirad (Institut Teknologi dan Kesehatan Muhammadiyah Kalimantan Barat, 2026)
Diabetes Mellitusis a chronic metabolic disease that requires long-term treatment and optimal patient adherence to prevent complications. Low medication adherence often becomes a major barrier to successful therapy. This study aimed to determine the effect of education delivered through video media on medication adherence among patients with Diabetes Mellitus in the working area of Puskesmas Perumnas, Kendari City. This research employed a pre-experimental design with a one-group pretest–posttest approach, involving 87 respondents selected using a purposive sampling technique. The independent variable was education using video media, while the dependent variable was medication adherence measured using the MMAS-8 questionnaire. The results showed that before receiving the educational intervention, most respondents had low (57.5%) and moderate (42.5%) adherence levels. Following the video-based education, adherence improved, with 63.2% categorized as high, 27.6% as moderate, and 9.2% as low. The Marginal HomogeneityTest yielded a p-valueof 0.000 (<0.05), indicating a significant effect of video-based education on improving medication adherence among patients with Diabetes Mellitus. In conclusion, education delivered through video media is effective in increasing medicationa dherence.